2021
DOI: 10.1163/22134913-bja10026
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Intersensory and Emotional Qualities of Everyday Objects: A Study on Smoothness or Sharpness Features with Line Drawings by Designers

Abstract: A large number of studies have focused on the aesthetic value of smoothly curved objects. By contrast, angular shapes tend to be associated with tertiary qualities such as threat, hardness, loudness, nervousness, etc. The present study focuses on the effect of curvilinearity vs angularity on the aesthetic experience of design artefacts. We used the drawings of everyday objects with novel shapes created by 56 designers (IUAV image dataset). Each drawing had two versions: a smooth and an angular version. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
3
5
0
Order By: Relevance
“…Participants liked the curved drawings more than the sharp-angled drawings. This result supports our hypothesis and previous literature using stimuli from the same image database Chuquichambi et al, 2021;Sinico, Bertamini, & Soranzo, 2021). In a broader sense, this finding is also in line with those from previous studies about the curvature effect using representational (Madani, 2007), and non-representational drawings (e.g., Corradi et al, 2019a).…”
Section: Discussionsupporting
confidence: 93%
“…Participants liked the curved drawings more than the sharp-angled drawings. This result supports our hypothesis and previous literature using stimuli from the same image database Chuquichambi et al, 2021;Sinico, Bertamini, & Soranzo, 2021). In a broader sense, this finding is also in line with those from previous studies about the curvature effect using representational (Madani, 2007), and non-representational drawings (e.g., Corradi et al, 2019a).…”
Section: Discussionsupporting
confidence: 93%
“…The authors interpreted the preference for rectilinear spaces in their study as the result of familiarity, which was previously found to be relevant for preference formation [ 34 , 38 ], although other studies investigating drawings of familiar objects have found it to modulate preference for curvature [ 33 ]. The sex effect was also found when presenting sketches of familiar objects, where females judged curvilinear objects as more peaceful than males [ 37 ]. Additionally, another recent study presenting abstract shapes as stimuli has found that curvature preference was stronger for female students in psychology [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have investigated the hypothesis that curved/rounded/curvilinear conditions are more appealing to humans than angular/edgy/rectilinear ones. This hypothesis has been shown to be correct using different types of visual stimuli including lines [ 14 , 15 , 16 , 17 , 18 ], font types [ 19 , 20 ], geometric shapes and simple forms [ 21 , 22 , 23 , 24 ], irregular shapes and meaningless patterns [ 3 , 4 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], images of familiar objects [ 3 , 26 , 31 , 32 , 33 , 34 , 35 , 36 ], sketches of familiar objects [ 33 , 37 ], in addition to sketches and images of designed products [ 38 , 39 ]. Different studies have found the effect to be present across species humans and apes [ 35 ], cultures—Western vs. non-Western [ 14 , 16 , 19 , 24 , 29 , 35 , 38 , 39 , 40 ], and ages—toddlers [ 27 ] and infants [ 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of stimulus material, previous research mainly adopted traditional presentation methods and used either matched but unrealistic stimuli with a limited number of images [e.g., N = 8 in Madani Nejad (2007) ; N = 4 in Dazkir and Read (2012) ], or a higher number of images of real environments at the (substantial) cost of accepting a considerable number of confounding factors ( Vartanian et al, 2013 , 2019 ), adding in both cases further limitations to the generalizability of results. Research investigating objects, on the other hand, ensured matched stimuli, and presented greyscale photographs of real objects ( Bar and Neta, 2007 ; Cotter et al, 2017 ) or line drawings ( Chuquichambi et al, 2021 ; Sinico et al, 2021 ). However, to the best of our knowledge, all previous studies were typically restricted to one image per environment/object, thereby showing stimuli exclusively from one side.…”
Section: Introductionmentioning
confidence: 99%